ANALISIS KINERJA KEUANGAN MENGGUNAKAN RASIO AKTIVITAS DAN PROFITABILITAS PADA ERISMART BANYUWANGI - Tri Rahayu Widyaningrum (NATUJA: Jurnal Ekonomi Syariah, 2024)
Financial performance is a priority for companies to maintain survival and increase expected profits. This research aims to determine the financial performance of Erismart Banyuwangi. The method used in this research is descriptive qualitative with financial ratio analysis tools, namely; activity ratio and Profitability Ratio. The primary data obtained is in the form of the Company's financial reports. Data collection techniques include interviews, observation and documentation. The data analysis instruments used are assessing the effectiveness of asset use using the Total Assets Turnover, Working Capital Turnover formulas and assessing profitability using the Return On Assets, Return On Equity formulas. The research results concluded that Erismart Banyuwangi had a good financial performance from each measuring instrument used.